KORELASI JARAK KEHAMILAN DAN KEPATUHAN MENGKONSUMSI TABLET FE TERHADAP KEJADIAN ANEMIA PADA IBU HAMIL - Asmi, A Syamsinar; Ethasari, Rossa Kurnia Ethasari; Anwar, Seniwaty; Inayati, Inna Noor; Resmi, Dewi Candra (Ensiklopedia of Journal, 2024)
Iron deficiency anemia is anemia that can be caused by iron deficiency in making haemoglobin levels, where iron is needed by the body, especially in making hem and globin. The preliminary survey obtained information on the presence of anemia patients <8 mg/dL totaling 28 cases, 8-11 mg/dL totaling 281 cases in the Tanah Merah Puskesmas work area. The purpose of the study was to determine the correlation between pregnancy spacing and compliance with taking Fe tablets to the incidence of anemia in pregnant women. The type of research used quantitative with a cross sectional approach. The research was conducted in March 2022 using stratified random sampling. The sample amounted to 189 people. The results showed there was a relationship between pregnancy distance (p value 0.000) and there was no relationship between Fe tablet consumption compliance (p value 0.245). It is suggested to the Health Office to be used as a program evaluation, to the puskesmas to be used as a reference in reducing the incidence of anemia, to researchers and further researchers to be used as evidence based. Keywords: Anemia, Pregnancy, Adherence, Fe Tablets